2021
DOI: 10.1111/anae.15475
|View full text |Cite
|
Sign up to set email alerts
|

The effect of respiratory activity, non‐invasive respiratory support and facemasks on aerosol generation and its relevance to COVID‐19

Abstract: Respirable aerosols (< 5 µm in diameter) present a high risk of SARS-CoV-2 transmission. Guidelines recommend using aerosol precautions during aerosol-generating procedures, and droplet (> 5 µm) precautions at other times. However, emerging evidence indicates respiratory activities may be a more important source of aerosols than clinical procedures such as tracheal intubation. We aimed to measure the size, total number and volume of all human aerosols exhaled during respiratory activities and therapies. We use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
115
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 42 publications
8
115
1
Order By: Relevance
“…The levels of environmental contamination in our study were not significantly influenced by CPAP/HFNO therapies and/or coughing. These findings broadly reflect data from aerosol generation studies in healthy adult volunteers which report non-invasive positive pressure ventilation (NIPPV) and HFNO did not generate significantly more aerosols (compared to other respiratory activities) 21 24 or in fact reduced emissions for NIPPV and HFNO 22 and CPAP 23 . This may be influenced by the semi-closed system of CPAP delivery and PEEP over the nose and mouth simultaneously that limit aerosol/droplet dispersion from respiratory secretions.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The levels of environmental contamination in our study were not significantly influenced by CPAP/HFNO therapies and/or coughing. These findings broadly reflect data from aerosol generation studies in healthy adult volunteers which report non-invasive positive pressure ventilation (NIPPV) and HFNO did not generate significantly more aerosols (compared to other respiratory activities) 21 24 or in fact reduced emissions for NIPPV and HFNO 22 and CPAP 23 . This may be influenced by the semi-closed system of CPAP delivery and PEEP over the nose and mouth simultaneously that limit aerosol/droplet dispersion from respiratory secretions.…”
Section: Discussionsupporting
confidence: 79%
“…Hamilton et al report HFNO was associated with increased aerosol emission (flow rate and machine dependent), however this was generated by the machine, not the patient, hence unlikely to carry SARS-CoV-2 virus. Moreover, these studies consistently reported the highest aerosol emissions were from coughing, irrespective of respiratory support modality, with at least a 3-fold increase [21][22][23] . We did not find this signal in our data however these findings indicate that coughing is potentially the most hazardous source of infectious SARS-CoV-2 aerosols to HCWs and not the respiratory support device itself.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast, the United States Centers for Diseases Control and Prevention (CDC), the European Centre for Disease Prevention and Control (ECDC), and the German Robert Koch Institute recommended universal use of ltering face piece class-2 (FFP-2) masks for protection against airborne transmission (19)(20)(21). Indeed, recent publications suggest that aerosols not arise only during AGP and therefore FFP-2 masks might be advantageous in virus-rich indoor environments including medical centres and hospitals (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Since the earliest days of the pandemic, respiratory droplets and fomites were assumed to be the major transmission routes, with airborne transmission only accepted within the limited confines of certain “aerosol generating procedures” 2 . In fact, this is a misnomer, because volitional coughing produces more aerosols than both invasive and non‐invasive respiratory therapies 3,4 . The experience of SARS and Middle East respiratory syndrome (MERS) should also have alerted us to the likelihood that SARS‐CoV‐2 could also be transmitted via the airborne route.…”
mentioning
confidence: 99%